Bioprocess for mass production and feed utilization of Azolla pinnata in aquaculture ponds: a perspective of bioeconomy and eco-friendly technology for small farms - Camargo, Tavani R. [UNESP]; Bueno, Guilherme Wolff [UNESP]; Machado, Levi P. [UNESP]; Brande, Maicon R. [UNESP]; Heitzman, Beatriz S. [UNESP]; Trombeta, Thiago D. (Universidade Estadual Paulista - Campus de Tupa, 2022)
Aquatic plants have a high potential to be used as eco-friendly technology in fish farming effluent treatment systems. However, there is still a reduced use of the vegetable biomass produced in these treatment systems. Thus, the aim of this study was to develop an alternative feed with the aquatic plant Azolla pinnata to take advantage of plant biomass, reusing the plant to develop a new product and promote a circular economy. A. pinnata was implemented in decantation pond that receives effluents from fish farming. Samples were collected weekly at four times (0, 7, 14, and 21 days). Posteriorly, A. pinnata was processed to obtain the meal. Azolla meal was offered along with three commercial feed (24%, 28% and 32% of the crude protein) in an experiment to evaluate the zootechnical performance of tilapia in small tanks. The results indicated that A. pinnata was efficient to retention of phosphorus and nitrogen after seven days. In the experiment with animals, the treatment using commercial feed with 28% of the crude protein + Azolla showed the best efficiency rates for using the diet. Thus, the use of the A. pinnata meal was a viable alternative in the search for sustainable products to promote a bioeconomy in the small fish farms.
Keywords: bioeconomy; circular economy; reuse effluents; sustainable aquaculture